2008
DOI: 10.3324/haematol.11849
|View full text |Cite
|
Sign up to set email alerts
|

An unusual hotspot in a young woman with Hodgkin's lymphoma

Abstract: A young woman has started cancer treatment because of a Hodgkin's lymphoma. After four months of chemotherapy, a PET scan showed an unexplained hotspot in the right lower abdomen. This was later explained by an unsuspected pregnancy. Our case emphasizes the importance of a pregnancy test in all women in the reproductive age before starting cancer treatment. Haematologica 2008; 93:e14-e15 DOI: 10.3324/haematol.11849 Introduction Malignancy during pregnancy is thought to be extremely rare. However, in the USA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Angel et al (39) used Monte Carlo simulations to estimate fetal dose in CT for a range of gestational ages and patient sizes and found no significant correlation between gestational age and fetal dose. For various fetal ages and maternal body habitus, the fetal dose estimates were between 1.1 and 21.9 mGy for CT. F-FDG PET studies of pregnant patients are extremely uncommon, and even 18 F-FDG PET studies accidentally performed on pregnant patients are rare (6)(7)(8)(9)(10)(11). Because adequate and accurate data regarding 18 F-FDG uptake by the fetus are not available other than the very few case reports of accidental exposure, it is difficult to get an estimate of fetal radiation exposure from 18 F-FDG PET in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angel et al (39) used Monte Carlo simulations to estimate fetal dose in CT for a range of gestational ages and patient sizes and found no significant correlation between gestational age and fetal dose. For various fetal ages and maternal body habitus, the fetal dose estimates were between 1.1 and 21.9 mGy for CT. F-FDG PET studies of pregnant patients are extremely uncommon, and even 18 F-FDG PET studies accidentally performed on pregnant patients are rare (6)(7)(8)(9)(10)(11). Because adequate and accurate data regarding 18 F-FDG uptake by the fetus are not available other than the very few case reports of accidental exposure, it is difficult to get an estimate of fetal radiation exposure from 18 F-FDG PET in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal dose estimates from CT have been based primarily on Monte Carlo simulations of geometric patient models (3)(4)(5). PET studies of pregnant patients are extremely uncommon, and even 18 F-FDG PET studies accidentally performed on pregnant patients are rare (6)(7)(8)(9)(10)(11). Therefore, providing fetal dose estimates from the CT and 18 F-FDG PET images themselves and from dose reports would be helpful to the medical imaging community.…”
mentioning
confidence: 99%
“…Abdominal and pelvic CT is associated with an average effective radiation dose of 25 mGy. Few studies have reported fetal radiation exposure during PET‐CT examinations, but these have calculated fetal doses in the range of 1‐21 mGy, which is significantly lower compared to the above‐mentioned adverse fetal effects threshold dose. While the performance of neck and chest CT scan beyond first trimester can be considered reasonable, abdominal‐pelvic CT is usually not recommended, especially up to week 17 of pregnancy …”
Section: Case I: Advanced Stage Newly Diagnosed Hl In the First Trimementioning
confidence: 98%
“…Total fetal irradiation was ten times less than the 100 mSv malformative risk limit described by the International Commission on Radiological Protection [4,5]. Depending on the FDG PET/CT procedure and fetal age, the fetal estimated dose ranged between 1.01 and 21.9 mGy in the 12 other published cases of FDG PET/ CT carried out during pregnancy that we found in the literature (Table 1) [5][6][7][8][9][10][11].…”
mentioning
confidence: 89%